2002
DOI: 10.1097/00002030-200209060-00010
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of HIV-1, HIV-2 and HIV-1/HIV-2 dually infected patients in a clinic-based cohort in The Gambia

Abstract: HIV-2-infected patients with CD4 cell counts of 500 cells/microl and greater had a significantly lower mortality rate than HIV-1-infected patients. HIV-2-infected patients with advanced disease had the same poor prognosis as patients with HIV-1. Dually infected patients had mortality rates similar to HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 27 publications
5
75
0
Order By: Relevance
“…The vast majority of HIV-2-infected individuals experience non-progressive disease [1] and the mortality rate of this subset is not significantly higher than the uninfected population [1,2]. HIV-2 can cause AIDS in a minority of infected individuals [3], however, most HIV-2-infected individuals behave as long-term non-progressors (LTNP).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of HIV-2-infected individuals experience non-progressive disease [1] and the mortality rate of this subset is not significantly higher than the uninfected population [1,2]. HIV-2 can cause AIDS in a minority of infected individuals [3], however, most HIV-2-infected individuals behave as long-term non-progressors (LTNP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HIV-2 appears slower to evolve the neutralization-resistant variant strains commonly found in HIV-1 infections (3,8). The rate of mother-to-child transmission is also much lower for HIV-2 (9), and differential neutralizing activities found in patients dually infected with HIV-1 and HIV-2 suggest the presence of distinct and divergent immune responses against these related viruses (10).…”
mentioning
confidence: 99%
“…Dual infection with HIV-1 and HIV-2 occurs mainly in West Africa, where the two viruses cocirculate. Several papers have indicated that dually infected patients have a disease course similar to that of patients infected with HIV-1 alone (21,52). The presence of HIV-2 in individuals dually infected with HIV-1 and HIV-2 complicates the treatment of these patients (53).…”
mentioning
confidence: 99%